Development and Feasibility Testing Of Liveworksheets Based E-LKPD For Learning To Make Sweet bread In Vocational Culinary School - Anifa Nur Fitri; Annisa Nur’ Aini; Lucia Tri Pangesthi; Aulia Bayu Yushila (Universitas Negeri Padang, 2026)
Advances in science and technology in 21st-century education require students to possess the 4C skills, therefore, digital learning media capable of supporting active, independent, and engaging learning are needed, particularly for the sweet bread curriculum in culinary vocational education, which demands a systematic procedural understanding. Sweet bread instruction is still dominated by conventional methods using simple worksheets that lack varied questions and clear visualizations of the process, resulting in low student engagement and difficulty in understanding the steps of making sweet bread. This study aims to: (1) develop a Liveworksheets-based E-LKPD for sweet bread production learning; (2) determine its feasibility in terms of content; (3) determine its feasibility in terms of media; and (4) analyze students responses. This Research and Development (R&D) study employed the ADDIE model, involving subject matter experts, media experts, and culinary students as research subjects. The validation data from the subject matter experts and media experts were analyzed using Aiken’s V index and the Intraclass Correlation Coefficient (ICC) reliability test, while the students’ response data were analyzed using percentage analysis. The results of the study indicate that the Liveworksheets-based E-LKPD was successfully developed with a content validity of 0,935 and a media validity of 0,889, both of which fall into the high category. The reliability test results showed an ICC value of 0,789 for the content aspect and 0,778 for the media aspect, indicating a good level of reliability. Student responses achieved a percentage of 78%, falling into the “very good” category. However, the ease-of-use aspect in both the media evaluation and student responses remained in the “moderate” category, thus requiring further refinement. This study has limitations because it was only conducted up to the development stage without testing effectiveness during the implementation stage through experimentation. The research findings indicate that the Liveworksheets-based E-LKPD on the topic of sweet bread is suitable for use as a digital learning medium with a high level of validity and excellent student responses, making it a viable alternative learning medium that supports 21st-century learning.